Prediction of blast loads on a deformable steel plate using Euler equations - (:unkn) unknown (My University, 2007)
The in-house computational fluid dynamics code PUMA2 was used to predict blast loads on a steel plate. In this study PUMA2 has been modified to include high temperature effects for air at equilibrium conditions in addition to the calorically perfect gas assumption. Preliminary tests performed for a planar shock wave and square cavity interaction agreed well with the experimental results. A blast simulation performed with the calorically perfect gas assumption in free air successfully predicted peak pressures with reasonable accuracy at various distances and qualitatively yielded the typical behavior of spherical blast waves. Finally blast loadings on a steel plate were predicted using calorically perfect gas and equilibrium air assumptions. Peak pressures yielded by these two solutions were similar and agreed well with predictions from the A.T.-Blast program, while the peak temperature predictions were quite different. Blast loads were used as input loads for the LS-DYNA finite element analysis code to investigate the effects of coating a steel plate using polyurea. Simulations performed for a steel plate with and without polyurea coating appear to demonstrate its effectiveness against fragmentation and failure due to air blast effects.